2017
DOI: 10.1111/jocn.13895
|View full text |Cite
|
Sign up to set email alerts
|

Levels of anxiety in parents in the 24 hr before and after their child's surgery: A descriptive study

Abstract: Aims and objectives: To (i) investigate pre-and postoperative anxiety levels in parents of surgical patients; (ii) identify factors that affect parental anxiety; and (iii) analyse assistance provided and overall parental satisfaction to assess whether and how this aspect can impact their anxiety level.Background: Surgery as an event generates anxiety in children and their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 55 publications
6
74
0
2
Order By: Relevance
“…Most factors identified in the current study have previously been identified as predictive of preoperative anxiety in children especially at induction of anesthesia . The original finding of this study is a combination of psychological factors and events leading to such anxiety, described via trait and state assessments at the preanesthetic consultation and on the day of surgery.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Most factors identified in the current study have previously been identified as predictive of preoperative anxiety in children especially at induction of anesthesia . The original finding of this study is a combination of psychological factors and events leading to such anxiety, described via trait and state assessments at the preanesthetic consultation and on the day of surgery.…”
Section: Discussionmentioning
confidence: 84%
“…Many risk factors have been investigated for preoperative anxiety in children. They include child age, child temperament, pharmacological premedication, maternal anxiety, lack of knowledge about the perioperative period, lack of knowledge about anesthetic practice—and in particular gas induction via face mask, and lack of knowledge about anesthetic and surgical safety . Subsequently, measures have been developed to reduce preoperative anxiety including premedication, preoperative workshops, distraction, clown doctors, parental presence during anesthesia induction, information leaflets, and video or web‐based content …”
Section: Introductionmentioning
confidence: 99%
“…In their study, Pomicino et al focused on the level of parental anxiety immediately before surgery. They also measured a higher level of anxiety in mothers than in fathers (OR = 4.7; P = .01) . It is of note that these four studies included all congenital malformations, and not only CHD.…”
Section: Discussionmentioning
confidence: 97%
“…This may reflect the quantity and quality of information given to parents during the preoperative visit, usually focusing on all potential complications. Indeed, the complexity of medical information provided to parents before their child's surgery, usually correlates with the level of parental anxiety, as shown by Pomicino et al Nevertheless, an inappropriate timing of the preoperative visit may play a more important role in parental anxiety than the level of medical information itself …”
Section: Discussionmentioning
confidence: 99%
“…State anxiety reflects unpleasant emotional arousal in face of threatening demands and dangers, whereas trait anxiety refers to a general tendency to respond with state anxiety in the anticipation of threatening situations and is a relatively stable characteristic of an individual. Parents of children undergoing surgery react in different ways to this threatening event (Pomicino et al, ). Parental trait anxiety is a good predictor of parental state anxiety on the day of surgery (Fortier & Kain, ).…”
Section: Introductionmentioning
confidence: 99%